Longitudinal dispersion of microplastics in aquatic flows using fluorometric techniques. (1st March 2020) - Cook, Sarah; Chan, Hui-Ling; Abolfathi, Soroush; Bending, Gary D.; Schäfer, Hendrik; Pearson, Jonathan M.
Abstract: Microplastics are an emerging environmental contaminant. Existing knowledge on the precise transport processes involved in the movement of microplastics in natural water bodies is limited. Microplastic fate-transport models rely on numerical simulations with limited empirical data to support and validate these models. We adopted fluorometric principles to track the movement of both fluorescent dye and florescent stained microplastics (polyethylene) in purpose-built laboratory flumes with standard fibre-optic fluorometers. Neutrally buoyant microplastics behaved in the same manner as a solute (Rhodamine) and more importantly displayed classical fundamental dispersion theory in uniform open channel flow. This suggests Rhodamine, a fluorescent tracer, can be released into the natural environment with the potential to mimic microplastic movement in the water column. Graphical abstract: Image 1 Highlights: Existing solute fluorometric techniques can be used to track microplastics. Neutrally buoyant polyethylene mimics solute movement. Harmless fluorescent tracer has the potential to be used as a microplastic proxy.